2015
DOI: 10.4209/aaqr.2015.11.0627
|View full text |Cite
|
Sign up to set email alerts
|

An Overview: Polycyclic Aromatic Hydrocarbon Emissions from the Stationary and Mobile Sources and in the Ambient Air

Abstract: Polycyclic aromatic hydrocarbons are a class of semi-volatile organic carbons that are emitted from both natural and anthropogenic sources therefore are ubiquitous in nature. Their main sources are both fossil and biomass fuels as well as other feedstocks used in chemical and combustion processes. Mostly the combustion processes are PAH depletion processes rather than PAH generating processes. PAHs are emitted from both stationary and mobile sources at varying levels depending on the operation conditions such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
90
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(95 citation statements)
references
References 183 publications
(343 reference statements)
2
90
2
1
Order By: Relevance
“…Wang et al indicated that the high affinities of polycyclic aromatic hydrocarbons (PAHs) to graphite sheets are dominated by π-π interactions. PAHs are also one class of semi-volatile organic compounds (Cheruiyot et al, 2015). Dioxin, is one of the organic compounds, which contains π electrons that can interact with π electrons of benzene rings of graphite sheets by means of π-π interaction (Wang et al, 2014b).…”
Section: Adsorption Mechanismmentioning
confidence: 99%
“…Wang et al indicated that the high affinities of polycyclic aromatic hydrocarbons (PAHs) to graphite sheets are dominated by π-π interactions. PAHs are also one class of semi-volatile organic compounds (Cheruiyot et al, 2015). Dioxin, is one of the organic compounds, which contains π electrons that can interact with π electrons of benzene rings of graphite sheets by means of π-π interaction (Wang et al, 2014b).…”
Section: Adsorption Mechanismmentioning
confidence: 99%
“…Among the most common atmospheric semi-volatile compounds, PAHs are ubiquitous pollutants from both natural and anthropogenic sources (Cheruiyot et al, 2015). Natural sources include forest fires, volcanic eruptions and degradation of biological materials.…”
Section: Introductionmentioning
confidence: 99%
“…The principle of flotation is based on the differences in surface hydrophobicity between the particles. The hydrophobicity and lipophilicity nature of PCDD/Fs and other organic contaminants such as PAHs, CBs, CPs and PCBs makes them easy to float into the froths after flotation (Cheruiyot et al, 2015;Lee et al, 2016). The previous report indicated that the flotation process could be successfully applied to substantially decrease the amount of carbon constituents and PCDD/Fs in HSWI fly ash (Liu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Due to small-scale incinerator, incomplete incineration and high chlorine content in the waste feed, some toxic persistent organic pollutants are generated such as polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans (PCDD/Fs), polycyclic aromatic hydrocarbons (PAHs), chlorobenzenes (CBs), chlorophenols (CPs) and polychlorinated biphenyls (PCBs), etc. (Lee et al, 2003;Chen et al, 2013;Cheruiyot et al, 2015;Lee et al, 2016). The PCDD/F emission factors of hospital solid waste incinerator (HSWI) were about 1-2 orders higher than those of municipal solid waste incinerator (MSWI) (Lee et al, 2003;Cheruiyot et al, 2016).…”
Section: Introductionmentioning
confidence: 99%